Independent Education: Predictions of the Needs-Based Independent Learning Curriculum Framework in Indonesia - Julduz Ruland Paus; Mint Husen Raya Aditama; Hary Dwi Estafianto (Universitas Negeri Semarang, 2023)
Merdeka Belajar is an educational program launched by the Minister of Education and Culture of the Republic of Indonesia. Merdeka Belajar prepares students to become strong graduates, relevant to the needs of the times, and ready to become leaders with a high national spirit. This research will reveal how Self-Education in the concept of Merdeka Belajar can improve students' hard skills and soft skills so that it can support the expansion of the Merdeka Belajar program. The results of measuring the need for soft skills and hard skills found the fact that factors of age, gender, and job status influenced the choice and needs in improving individual soft skills and hard skills. Factors such as leadership, determination, self-control and self-organization, work independence, and employability are the dominant factors used in the defensive approach to the development of self-education. This study shows that a Self-Education curriculum based on the need for soft skills and hard skills must be carried out consistently and regularly. Further research on Self-Education needs to be given special attention in developing more complex and diverse models, especially in the pedagogical skills of teachers as independent mentors of students, especially in non-formal educational institutions.